Find the general solution to y'' + 4y' + 3y = x.
Genral solution "y(x)" is the sum of the general solution "y_g(x)" of homogeneous equation "y'' + 4y' + 3y =0" and the partial solution "y_p(x)" of non-homogeneous equation "y'' + 4y' + 3y = x":
Let the partial solution be "y_p(x) = \\dfrac13x-\\dfrac49" (one can verify by direct substitution).
To find the general solution let's solve the characteristic equation:
Thus, obtain:
Finally:
Answer. "y(x) = Ae^{-x} + Be^{-3x} + \\dfrac13x-\\dfrac49".
Comments
Leave a comment